Chemical Composition and Bioactivity of Essential Oil of Ageratina adenophora from Bhaktapur District of Nepal - Subba, Bimala; Kandel, Ram Chandra (Journal of Nepal Chemical Society, 2013)
The essential oil of Ageratina adenophora locally call Banmara was analyzed by GC–MS. A total of 45 volatile compounds was identified and torreyol (16.8%) was the major component in oil. The sesquiterpene fraction was higher than the monoterpene one. The essential oil showed significant antibacterial activity against both gram positive (Klebsiella pneumoniae and Staphylococcus aureus) and gram negative (Escherichia coli and Proteus vulgaris) bacteria. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9350 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 78-86 Uploaded date: 12/18/2013